1. Genthelvite from the Ilímaussaq Alkaline Intrusion, South Greenland. - Bollingberg, H.; Petersen, Ole V, (Meddelelser om Grønland, 1967)
Tiny white or yellow grains of genthelvite have been found in cavities in albititic veins in the Ilímaussaq alkaline intrusion. The veins also contain oogirine, neptunite, catapleiite, eudidymite, epididymite, tugtupite and leucophane. The mineral has been identified by means of x-ray and spectrographic methods.